(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The twenty-first century Art and Design education for learners with disabilities has to swivel from just being a psychomotor remedy to assessable and skills oriented subject in special schools. This change is in sync with many educationists who view quality Art and Design education as a platform for helping learners to fully develop, including those with disabilities. Through quality Art and Design education, learners with disabilities are not only uplifted educationally but also socially, psychologically, intellectually and physically. Hence, this study assessed the provision of quality Art and Design education among physically challenged Ordinary Level learners in a Bulawayo Central District school in Zimbabwe. Interpretivist paradigm, qualitative approach and case study design were adopted. Thematically analysed data were collected through semi-structured interviews, focus group discussions and document analysis. Purposively chosen sample comprised sixteen physically challenged Ordinary Level Art and Design learners, two Art and Design teachers, two school administrators, one subject inspector, one physio-occupational therapist and three School Development Committee members. Findings reveal that active learning methodologies, low teacher-learner ratio, assessment practices and adaptable environment enhanced quality Art and Design education to physically challenged learners at the school understudy. However, inadequacy of assistive devices, human and instructional resources, and lack of support from other stakeholders compromised the quality of Art and Design education among physically challenged Ordinary Level learners at the school. The study concluded that though the selected school encountered some constraints in providing quality Art and Design education to physically challenged learners there were noticeable good practices adopted.